PARTICIPATIVE BUDGETING AS AN INSTRUMENT OF BROADENING THE STRUCTURE OF POLITICAL OPPORTUNITIES: CASE OF SAINT-PETERSBURG - Aleksandr V. Kurochkin; Ivan A. Roshchupkin (Вестник Московского государственного областного университета, 2019)
In the article the authors analyze the phenomenon of participatory budgeting in the context of global digitalization and networking of political decision-making at all levels of government. For Russia these processes are understood to be twice as important and actual as the regime of sanctions make accumulation and diligent use of internal resources critical for the economy development. As a methodological basis of the study the concept of network political governance was used, as well as the matrix of political opportunities, which provides researchers with a kind of system of coordinates, within which it is possible to answer the question about the causes and dynamics of social movements. The prospect of implementing the projects of civil initiatives is also clarified within it. Special attention is given to the process of institutionalization and participatory budgeting practices implementation. It reflects such components of the structure of political possibilities matrix as: the degree of administrative-bureaucratic system resistance, as well as the level of openness and responsiveness of government. As a result of the analysis, the authors came to the conclusion that the implementation and further development of the participatory budgeting institution can significantly affect the structure of political opportunities in the process of transition to a network model of political governance. It can be defined not only as an effective tool for budget saving and its more detailed distribution, but for depolarization and reduction of social tension. The latter is especially important for the balanced social-economic and political development of large urban centers, as the experience of St. Petersburg clearly shows.